If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = 6x + 16 Reorder the terms: -6 + 2x = 6x + 16 Reorder the terms: -6 + 2x = 16 + 6x Solving -6 + 2x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 2x + -6x = 16 + 6x + -6x Combine like terms: 2x + -6x = -4x -6 + -4x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + -4x = 16 + 0 -6 + -4x = 16 Add '6' to each side of the equation. -6 + 6 + -4x = 16 + 6 Combine like terms: -6 + 6 = 0 0 + -4x = 16 + 6 -4x = 16 + 6 Combine like terms: 16 + 6 = 22 -4x = 22 Divide each side by '-4'. x = -5.5 Simplifying x = -5.5
| 10x+10=x-10 | | 8n^2-8n+5=0 | | 4p+2q=-28 | | x+2=-x+4 | | x(x)+y(y)=40 | | 9b-7b=16 | | 12.50-(2.50x)=7.50 | | 12.50-(2.50x)=750 | | 3x+8=0.5(2x)+24 | | y-3x=-17 | | 2x-5+5y=37 | | 4x+18-x=24 | | V=8y^3+38y^2+9y | | 6-(5x+3)=9-7x | | -3(-7u+9)-6u=7(u-3)-4 | | 319=c-253 | | 5(2x+3)=11x-(X-15) | | -2(t+2)+5*t=6*t+11 | | -x+1=5x-8 | | 2+4x-2x^2=2-2x | | 18x+24x+12x+6x=360 | | 16-b=15 | | 3x-7y-8x-y= | | 2x-6=6x+16 | | p+p=19-1 | | 5x+3y(5x*5y)=300 | | 5x+3y(5x*5y)=200 | | 5x+3y(5x*5y)=20 | | 7m+10=31 | | 6x-5=14x+25 | | 7t+7=21 | | 2(lnx^3)-lnx+3=7 |